ANALISIS SPIRITUAL CHARACTER PELAKU ISBAT NIKAH DI PENGADILAN AGAMA WATAMPONE - A. Sri Mardiyanti Syam (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2021)
AbstractRegarding the marriage legalization cases in the Religious Court of Watampone, if the formal requirements have been met, then the religious court by the judges will make a verdict or decision of which written "the applicationis approved". Meanwhile, if the formal requirements are not met, then the judge will make a verdict or decision declaring that "the application is overruled". Judge in deciding a case will pay attention on posita and should be in accordance with existing procedures, among others, present witnesses at the hearing and show that there is evidence for consideration. The judge will put forward maqasid syari’ah, so that the impact will be on the benefit of generations, to keep and maintain the honor that will be seen in the decision or verdict of the judge who accepted and granted other. Therefore, marriage legalization in principle is one of the legal protection, as referred to in Article 7 KHI, toward a marriage that cannot be proven with a marriage certificate as an authentic document in accordance with the mandate of Marriage Act.